Trunk/Legs Dual Energy X-Ray Absorptiometric Index Of Abdominal Obesity In Diagnosing Visceral Obesity In Cushing’s And Obese Women - Slavica Shubeska Stratrova; Sasha Mishevska Jovanovska; Dejan Spasovski; Maja Dimitrovska (My University, 2020)
Objectives: Obesity and especially central body fat distribution (BFD) are known risk factors for cardiovascular and metabolic diseases. Android obesity in Cushing’s syndrome (CS) and in non CS abdominally obese women with the metabolic syndrome, which is predominantly visceral, intra-abdominal, is more predictive of adipose-related comorbidities than gynecoid obesity, which has a relatively peripheral (gluteal) distribution. Determination of dual-energy x-ray absorptiometric (DXA) indexes cut-off point values of abdominal obesity is very important to discover obese women with abdominal obesity. The aim of this study was to determine cut-off point values of DXA indexes of central, abdominal obesity determined as a ratio of trunk to legs tissue and fat mass and their percentages that best differentiate CS and O and confirm central, abdominal obesity. Material and Methods: DXA assessment of body composition and BFD was performed in two groups of women, each consisting of 21 subjects: 1st group of CS with clinically confirmed CS with Body Mass Index (BMI) (30.03±6.49 kg/m2 ) and age of 42.98±13.27 years and 2nd group of obese women (O), matched with CS according to their BMI (29.91±6.12 kg/m2 ) and age (41.04±12.85 years). Trunk/Legs tissue mass ratio (Tr/L-T), trunk/legs fat mass ratio (Tr/L-F), trunk/legs tissue % fat mass ratio (Tr/L-T%f) and trunk/legs fat mass % ratio (Tr/L-F%) were determined as indexes of central, ab - dominal obesity and their cut-off point values that best differentiate CS women from O were also determined. Sensitivity (S), specificity (Sp), positive predictive value (PPV), negative predictive value (NPV) and DG (diagnostic accuracy) of these idexes were determined. Results: Tr/L-T values in CS were 2.05±0.44, significantly higher compared to 1.42±0.28 in O, and Tr/L-F values in CS 2.33±0.55 were also significantly higher compared to O (1.39±0.66) (p<0.0001). Tr/L-T%f values in CS were 1.15±0.14, significantly higher compared to 0.94±0.22 in O, as well as Tr/L-F% values of 1.18±0.12 in CS were significantly higher compared to O (0.94±0.68) (p<0.0001). Tr/L-T cut-off point value of 1.6 best differentiated CS from O for DG of 88.89% and Tr/L-F cut-off point value of 1.8 best differentiated CS from O for DG of 88.89%. Tr/L-T%f value of 1.0 differentiated CS from O for DG of 72.22% and Tr/L-F % value of 1.1 differentiated CS and O for DG of 77.78%. Tr/L-T and Tr/L-F differentiated CS and O with higher diagnostic accuracy. Tr/L-T with higher sensitivity of 94.44% and NPV value of 93.75% differentiated CS from O compared to the Tr/L-F correspondent values 83.33% and 85%. Conclusion: Tr/L-T and Tr/L-F DXA indexes cut-off point values of 1.6 and 1.8 best differentiated CS women from matched O women with high diagnostic accuracy. They confirmed abdominal, visceral obesity in CS with significantly higher values in CS compared to obese women and could be used as diagnostic indexes of abdominal obesity. Tr/L-T%f and Tr/L-F% indexes differeniated the two examined groups with lower diagnostic accuracy and are not useful in diagnosing abdominal obesity.
Keywords: Cushing’s Syndrome; abdominal obesity; dual-energy x-ray absorptiometry